The impact of quality signals on the performance of COVID-19 related crowdfunding - Suhaili Alma’amun,; Mohd. Khairy Kamarudin,; Suaibatul Aslamiah Achni,; Siti Nur Fatin Atirah Rosli, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to examine the impact of quality signals on crowdfunding performance. The data are based on 80 projects gathered from three Malaysian donation-based crowdfunding platforms that use a keep-it-all funding approach. OLS regression is used to estimate the relationship between quality signals on crowdfunding performance. The data was collected during the early stages of the COVID-19 pandemic. The study finds that crowdfunding performance is influenced by six quality signals: funding goals, word count, social networks, updates, comments, and campaign duration. This study adds to the empirical literature in signaling theory within the context of donation-based crowdfunding. It enriches the specific information about quality signals that are capable of increasing the performance of COVID-19-related crowdfunding in Malaysia which has remained unidentified in the previous studies. The success of campaigns is important to fundraisers, and to increase the chances of obtaining more fundimg, fundraisers should send quality signals to the potential funders.